An Analysis of Environmental Pollution Laws and Regulations in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The Nigerian environment faces a multitude of severe pollution challenges, including pervasive oil spillages, continuous gas flaring, desertification, drought, climate change impacts, escalating municipal waste generation, and gully erosion. These persistent problems are exacerbated by rapid population growth and the relentless exploitation of natural resources. In response, the Nigerian government has enacted a suite of environmental pollution prevention laws and established regulatory bodies designed to abate environmental degradation. This paper examines the concept of the environment and its components, defines pollution and its various types, and investigates the primary causes of environmental pollution in Nigeria. It provides a critical analysis of the key environmental pollution prevention laws and regulations, evaluating their effectiveness in stemming the tide of environmental degradation. The analysis reveals that while a comprehensive legal framework exists on paper, its effectiveness is critically undermined by outdated provisions, weak enforcement mechanisms, constitutional limitations, and a lack of political will. The paper advocates for significant legal and policy reforms, including the strengthening of institutional capacity, enhanced public participation, and a renewed commitment to the sustainable use and conservation of natural resources to achieve a more effective environmental enforcement regime in Nigeria.